1994
DOI: 10.1007/bf01426396
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation induced photoionization and photodissociation of carbon monoxide in the 14–35 eV region

Abstract: Abstract. Carbon monoxide has been excited with monochromatic synchrotron radiation in the 14-35 eV range using the Swedish synchrotron facility MAX in Lund. The decay products were studied in various detection channels such as formed CO + and C + ions using mass spectroscopy and visible or VUV fluorescence using photon detection. A rich line structure is observed which is attributed to CO Rydberg series converging to the X, A, B, D, C and E states in CO +. While a great number of these lines are already known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
(33 reference statements)
5
27
1
Order By: Relevance
“…Different Hamamatsu PM tubes were used for various wavelength regions R1080 ͑1150-3200 Å͒, R1081 ͑1150-2000 Å͒, and R647 ͑3000-6500 Å͒. This system has earlier been used in similar investigations for instance of N 2 , 28,29 O 2 , 30,31 CO, 32 and CO 2 . 33 A closer description of the experimental setup is found in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Different Hamamatsu PM tubes were used for various wavelength regions R1080 ͑1150-3200 Å͒, R1081 ͑1150-2000 Å͒, and R647 ͑3000-6500 Å͒. This system has earlier been used in similar investigations for instance of N 2 , 28,29 O 2 , 30,31 CO, 32 and CO 2 . 33 A closer description of the experimental setup is found in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…27 Using mass spectroscopy, Sha and co-workers 11 detected both C ϩ and O ϩ photofragments after 2ϩ1 REMPI of CO at 230 nm and determined the pulse-energy dependence for the corresponding photofragment yields. Their results suggest that all photodissociation channels in Eqs.…”
Section: ͑3͒mentioning
confidence: 99%
“…The undispersed VUV fluorescence in the range from 105 to 200 nm has been detected by a CsI-coated microchannel plate (MCP) behind a LiF window. Absolute wavelengths of the monochromatized SR have been calibrated by matching observed peak energies with the well known energies of some vibronic levels of Rydberg states converging to the CO + (B) state (Ogawa and Ogawa 1972, Ito et al 1985, Erman et al 1994 between 19 and 19.6 eV. PIFS spectra have been taken using a 20 cm Seya-Namioka monochromator for dispersing and a position-sensitive detector (Ukai et al 1992a) for recording the fluorescence with a typical resolution of 1.3 nm.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…In Ehresmann et al (1995) the problem of assigning the different observed line structures in the cross sections to specific superexcited states of CO has been shared out and available assignments from literature have been used. However, in a very recent publication, Erman et al (1994) pointed out the necessity of a reassignment of the observed line structures. Based also on a very recently published high-resolution photoelectron study of Baltzer et al (1994) they reassigned line structures observed in their photoion spectra and their measurements of the undispersed fluorescence excitation as a function of the exciting-photon energy (FE function) to some vibrational levels of CO Rydberg states converging to the D, C, and E states of CO + .…”
Section: Introductionmentioning
confidence: 99%